The double torsion test applied to fine grained freshwater columnar ice, and sea ice - Parsons, B. L.; Snellen, J. B.; Muggeridge, D. B. (National Research Council of Canada. Institute for Marine Dynamics, 1988)
The Double Torsion fracture test geometry has been applied to samples of fine grained fresh water ice grown in the cold room, and to first year sea ice tested in situ at 74°N. The lab ice was grown at -20°C from a wet seed, and sample dimensions of 0.05m × 0.5m × 1.0m were used for both ices in the test rig. No stable sub-critical crack growth was observed, cracks extended in a slip-stick manner. No creep fracture was observed. The fracture toughness was found to increase with duration of loading to growth initiation, but the arrest stress intensity factor showed no load rate dependence. Crack jump length was found to be correlated to the drop in stress intensity factor, but not to load rate. The arrest stress intensity factor appears to be the creep free fracture toughness, and was the same for both types of ice. Peer reviewed: No NRC publication: Yes